2011
DOI: 10.1177/1753193411406632
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical assessment of gap formation after flexor tendon repair using partial interlocking cross-stitch peripheral sutures

Abstract: The gap formation of five core plus peripheral suture techniques for flexor tendon repair was evaluated by cyclic load testing. Fifty pairs of dental roll tendon models were sutured using six-strand Pennington modified Kessler core suture with 4-0 Polypropylene. One-half or three-fourths circumferential interlocking cross-stitch, or three complete circumferential peripheral suture techniques were performed using 6-0 Polypropylene. An initial cyclic load of 10 N for 500 cycles was applied and increased by 5 N f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Ansari et al (2009) showed that the use of circumferential repairs covering only the palmar half of the tendon surface could significantly increase the gap resistance and thus can be used together with a complex core suture, though a complete peripheral repair was even more effective in resisting gap formation at the repair site. Takeuchi et al (2011) found that a complete circumferential repair with interlocking crossstitches was better than a peripheral suture covering only one-half or two-thirds of the tendon circumference. Wit et al (2013) found that the geometry of core sutures has a great influence on the strength, but peripheral sutures did not have a significant mechanical effect on the tested core sutures.…”
Section: Peripheral Repairsmentioning
confidence: 93%
“…Ansari et al (2009) showed that the use of circumferential repairs covering only the palmar half of the tendon surface could significantly increase the gap resistance and thus can be used together with a complex core suture, though a complete peripheral repair was even more effective in resisting gap formation at the repair site. Takeuchi et al (2011) found that a complete circumferential repair with interlocking crossstitches was better than a peripheral suture covering only one-half or two-thirds of the tendon circumference. Wit et al (2013) found that the geometry of core sutures has a great influence on the strength, but peripheral sutures did not have a significant mechanical effect on the tested core sutures.…”
Section: Peripheral Repairsmentioning
confidence: 93%
“…Biomechanical testing under cyclic loading. Immediately after completion of the sutures, the sutured rolls were mounted on a custom-made cyclic loading machine (Takeuchi et al, 2010(Takeuchi et al, , 2011). Both roll ends were gripped using two upper and lower clamps to prevent slippage.…”
Section: Group Divisions and Repair Methodsmentioning
confidence: 99%
“…The dental roll tendon, Parotisrolls TM (Coltene/Whaledent Gmbh+CO., Germany) consisted of compact cotton wool, and are used for dental treatment. This roll tendon has been used for biomechanical evaluation of tendon repair strength (Takeuchi et al, 2010(Takeuchi et al, , 2011Tare, 2004). A total of 120 rolls were used in six groups of 20 rolls.…”
Section: Part 1 Test Using Dental Rollsmentioning
confidence: 99%
“…Dear Sir, We read with interest the published articles by Takeuchi et al on mechanical improvements on epitendinous tendon repair techniques (Takeuchi et al, 2010(Takeuchi et al, , 2011. The tendon model used in these experiments was an artificial cotton roll model (Parotisroll™, Coltene/ Whaledent Gmbh + Co., Germany).…”
Section: Evaluation Of the Artificial Cotton Roll Tendon Model For Mechanical Tendon Repair Experimentsmentioning
confidence: 99%